DETERMINANTS OF COMPLIANCE WITH PERSONAL TAX OBLIGATION: DO TAX AMNESTY PLAY? - Resshe Serlly Gita; Amir Hidayatulloh (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2019)
This study aims to analyse the effect of tax services, tax amnesty, taxation knowledge, and tax sactions on taxpayer compliance. The population in the study is an individual taxpayer in the city of Yogyakarta. The sample in the study was an individual taxpayer in the city of Yogyakarta, and took part in the tax amnesty program. The sampling technique in this study used the convenience sampling method. Responden in the study amounted 60 respondents. The data anlysis technique in this study used multiple linear regression analysis. This study obtained result that taxpayer compliance in influenced by tax services and tax amnesty programs. However, taxation knowledge and tax saction does not affect taxpayer compliance. The cause of taxation knowledge does not affest taxpayer compliance, perhaps the understanding of taxpayers regarding the procedures for payment and reporting is still minimal. Meanwhile, the reason for lack of support fot tax sanction on taxpayer compliance, perhaps because taxpayers consider that saction given when taxpayer violate laws are still mild. Therefore, these two reasons are factors that encourage taxpayers to behave disobediently.